Implementasi Good Handling Practices sebagai Upaya Optimalisasi Penanganan Pascapanen Jeruk Lemon: Implementation of Good Handling Practices as an Effort to Optimize Postharvest Handling of Lemons - Napitupulu, Tia Sofiani; Sumarlina, Sumarlina; Nadhirah, Aulia; Marseva, Amalia Dwi; Nuruzzaman, Harish (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Politeknik Negeri Jember (Polije), a competency-based higher education institution, has developed a Teaching Factory (TeFa) with various forms and types of products. TeFa Kebun Inovasi consistently produces various food and horticultural crop products, including lemons. The problem is that post-harvest handling of lemons still needs to be improved, impacting product quality. Apart from that, the still low demand for lemons is also a challenge that needs to be resolved. Therefore, efforts are being made to optimize post-harvest lemon handling by implementing Good Handling Practices (GHP). The method for implementing service activities is through direct assistance, evaluation, and feedback from the service team to partners. The results of service activities include (1) mentoring activities were participated in by partners (Innovation Garden management staff) and were carried out well; (2) the success of mentoring activities is measured using six indicators, namely skills in detecting fruit that meets harvest criteria, skills in harvesting according to procedures (SOP), skills in sorting and grading, labeling, and skills in storing and packaging; and (3) the evaluation results show that there is a significant increase in skills in terms of post-harvest handling of lemons at TeFa Kebun Inovasi dan Nursery Kebun Potong before and after the implementation of service activities.